Case report on necrotizing fasciitis following episiotomy - Pegu, Bhabani; D., Jayalakshmi; Gupta, Avantika (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Necrotising fasciitis (NF) is an extremely rare but near fatal bacterial soft tissue infection, complicating the operative wounds. Here is a case report of Necrotising fasciitis in episiotomy wound in low socioeconomic, poorly nourished and anaemic women. A 39 years old, second gravida, delivered normally with medio-lateral episiotomy under local anaesthesia. On postnatal day four, patient developed high grade fever and on examination episiotomy was found to be unhealthy and gaped. She was started on broad spectrum antibiotics empirically but the cellulitis rapidly progressed to vulva, then to the bilateral thighs and extended till knees. Bilateral lower limb Doppler ultrasonography was done to rule out deep vein thrombosis which showed no abnormality. USG abdomen revealed huge pus collection in the lower abdomen. Under anaesthesia, surgical exploration was done, pus was drained followed by wound debridement and pus sent for culture and sensitivity. Pus and blood culture showed growth of Klebsiella pneumoniae, so started on appropriate antibiotics. Patient started recovering, when the wound was healthy, secondary suturing of episiotomy wound done. She was discharged on post-natal day 27 after full recovery. Early diagnosis and aggressive timely management are the corner stone to avoid morbidity and mortality of NF.